Change of refractive indices in ternary mixtures containing chlorobenzene + n-hexane + (n-heptane or n-octane) at 298.15 K - Touriño A.; Hervello M.; Moreno V.; Marino G.; Iglesias M. (Journal of the Serbian Chemical Society, 2004)
The refractive indices of ternary mixtures of chlorobenzene + n-hexane (n-heptane or n-octane) have been measured at 298.15 K and at atmospheric pressure over the whole composition diagram. Parameters of polynomial equations which represent the composition dependence of physical and derived properties are gathered. The experimental refractive indices and the ternary derived properties are compared with the data obtained using several predictive semi-empirical models. The use of the Soave–Redlich–Kwong (SRK) and the Peng–Robinson (PR) cubic equations of state with the Van der Waals one-fluid mixing rule, which incorporate different combining rules to predict refractive indices on mixing, are tested against the measured results, good agrement being obtained.